Perovskite cell based on fullerene-based hybrid electron transport layer and preparation method thereof

CN122935111APending Publication Date: 2026-10-16WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610928721.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,现有富勒烯类电子传输材料在实际应用中仍存在一定局限

Benefits of technology

[0023]在本发明中,阴极缓冲层和银电极均采用热蒸发法制备得到,该方法设备简单、沉积速率高,有助于大幅降低制造成本,推动钙钛矿电池的规模化量产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122935111A_ABST
    Figure CN122935111A_ABST
Patent Text Reader

Abstract

The application discloses a perovskite cell based on a fullerene-based hybrid electron transport layer and a preparation method thereof. The preparation method of the perovskite cell based on the fullerene-based hybrid electron transport layer comprises the following steps: sequentially preparing a hole transport layer and a perovskite light absorption layer on a pretreated substrate; mixing L8BO-DC 60 powder with an organic solution of PCBM to obtain a mixed solution with a concentration of 1-3 wt%; spin-coating the mixed solution on the perovskite light absorption layer to obtain a fullerene-based hybrid electron transport layer after drying; and sequentially preparing a cathode buffer layer and a silver electrode on the fullerene-based hybrid electron transport layer. 60 The application constructs a PCBM:L8BO-DC 60 hybrid electron transport layer, effectively improves perovskite film morphology and interface energy level matching, enhances electron transport capacity, and thus significantly improves photovoltaic performance and environmental stability of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of perovskite solar cell photovoltaic technology, and particularly relates to a perovskite solar cell based on a fullerene-based hybrid electron transport layer and its preparation method. Background Technology

[0002] Against the backdrop of continuously growing energy demand and increasingly prominent environmental problems, developing clean, efficient, and sustainable new energy technologies has become an important development direction. Solar energy has received widespread attention due to its abundant resources and clean, safe operation. Among them, perovskite solar cells, as an emerging photovoltaic technology, show promising application prospects due to their advantages such as high photoelectric conversion efficiency, high material utilization, low-temperature solution processing capability, and great potential for flexible fabrication.

[0003] The performance of perovskite solar cells depends not only on the perovskite light-absorbing layer itself but also on the material properties and film quality of the interfacial charge transport layer. Among these, the electron transport layer plays a crucial role in electron extraction, transport, and suppression of interfacial carrier recombination. Fullerenes and their derivatives, due to their high electron affinity, good electron transport capabilities, and energy level structures well-matched to perovskite materials, are widely used as electron transport layers in inverted perovskite solar cells. However, existing fullerene-based electron transport materials still have certain limitations in practical applications. On the one hand, fullerene molecules tend to aggregate, resulting in poor coverage and uniformity of the formed film, which is not conducive to constructing continuous and dense electron transport channels, thus affecting electron extraction and transport efficiency. On the other hand, there is still room for improvement in the interface control, electrical performance, and environmental stability of traditional fullerene electron transport layers, which to some extent restricts further improvements in the efficiency and long-term stability of perovskite solar cells.

[0004] In summary, developing a fullerene-based hybrid transport layer material suitable for perovskite solar cells, possessing good film-forming properties, charge transport capability, and stability, and its preparation method, is of great significance for improving the overall performance of perovskite solar cells. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a perovskite solar cell based on a fullerene-based hybrid electron transport layer and its fabrication method. This invention utilizes a fused-ring bridging double-sphere fullerene L8BO-DC... 60 Introducing fullerene derivative [6,6]-phenylC 61 In methyl butyrate (PCBM), PCBM is constructed as: L8BO-DC 60Hybrid transport layer. This hybrid transport layer can improve the morphology of the transport layer film, enhance the uniformity and density of the film, and improve the electron transport capability and interface charge extraction efficiency, thereby helping to improve the short-circuit current density, open-circuit voltage and fill factor of perovskite solar cells, and further improve the photoelectric conversion efficiency and operating stability of the device.

[0006] The objective of this invention is achieved through the following technical solution: A method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer includes the following steps: (1) A hole transport layer and a perovskite light-absorbing layer are sequentially prepared on the pretreated substrate; (2) L8BO-DC 60 The powder was mixed with an organic solution of PCBM to obtain L8BO-DC. 60 A mixed solution with a concentration of 1~3 wt% was prepared; the mixed solution was spin-coated onto the perovskite light-absorbing layer described in step (1), and dried to obtain a fullerene-based hybrid electron transport layer. (3) A cathode buffer layer and a silver electrode are sequentially prepared on the fullerene-based hybrid electron transport layer described in step (2) to obtain a perovskite battery based on the fullerene-based hybrid electron transport layer.

[0007] In this invention, the L8BO-DC 60 The chemical molecular structure is shown below: .

[0008] Preferably, the substrate in step (1) is indium tin oxide (ITO) conductive glass.

[0009] Preferably, the substrate in step (1) undergoes the following pretreatment: sequential cleaning, drying and ultraviolet light treatment.

[0010] In some embodiments of the present invention, the substrate is subjected to cleaning, drying and ultraviolet light treatment, the purpose of which is to thoroughly remove organic pollutants and particulate impurities from the substrate surface, improve surface wettability, and thereby improve the film quality and interfacial contact performance of subsequent functional layers.

[0011] Preferably, the thickness of the hole transport layer in step (1) is 5~10 nm.

[0012] In some embodiments of the present invention, the thickness of the hole transport layer in step (1) is 5~10 nm, for example, it can be 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, and 10 nm, or any value between any two of the above. Controlling the hole transport layer thickness to 5~10 nm is mainly to significantly reduce the absorption and reflection losses of light by the material while ensuring the film is dense and effectively blocks electrons, thereby allowing more light to enter the light-absorbing layer and increasing the short-circuit current of the battery. At the same time, the ultra-thin structure can also reduce the use of hygroscopic dopants, effectively reducing the corrosion of the device by moisture, and significantly improving the photoelectric conversion efficiency and long-term stability of the battery.

[0013] Preferably, the hole transport layer in step (1) is prepared by the following steps: MeO-2PACz is dissolved in anhydrous ethanol to prepare a precursor solution, the precursor solution is spin-coated onto the pretreated substrate, and then the substrate is annealed at 100°C for 10 min and naturally cooled to room temperature to form a hole transport layer.

[0014] Preferably, the thickness of the perovskite light-absorbing layer in step (1) is 300 nm.

[0015] Preferably, the perovskite light-absorbing layer in step (1) is prepared according to the following steps: 387.2 mg PbI2, 176.3 mg FAI, 53.0 mg CsI and 132.1 mg PbBr2 are weighed and added to 1 mL of a mixed solvent with a DMF:DMSO volume ratio of 4:1. After complete dissolution, a perovskite precursor solution is obtained. The obtained solution is stirred at room temperature for 4-6 h and filtered through a 0.22 μm filter membrane before use. 50-60 μL of the above perovskite precursor solution is dynamically dropped onto the surface of the hole transport layer and spin-coated at 3000 rpm for 30 s. 5 s before the end of spin-coating, 100-150 μL of chlorobenzene (CB) is dropped onto the surface of the perovskite wet film as an antisolvent. Subsequently, the obtained perovskite film is annealed in a glove box at 100°C for 10 min to obtain the perovskite light-absorbing layer.

[0016] Preferably, the concentration of the organic solution of PCBM in step (2) is 20 mg / mL.

[0017] Preferably, the solute in the organic solution of the PCBM in step (2) is one of chlorobenzene, chloronaphthalene and o-dichlorobenzene.

[0018] Preferably, the thickness of the fullerene-based hybrid electron transport layer in step (2) is 50~60 nm.

[0019] In some embodiments of the present invention, the thickness of the fullerene-based hybrid electron transport layer in step (2) is 50-60 nm, for example, it can be 50 nm, 51 nm, 52 nm, 53 nm, 54 nm, 55 nm, 56 nm, 57 nm, 58 nm, 59 nm and 60 nm, or any value between any two of the above. Controlling the thickness of the fullerene-based hybrid electron transport layer to 50-60 nm is mainly to achieve the best balance between suppressing interfacial leakage and ensuring efficient electron transport, ensuring both a dense, pinhole-free film and maintaining a low series resistance.

[0020] Preferably, the thickness of the cathode buffer layer in step (3) is 5~7 nm.

[0021] Preferably, the cathode buffer layer in step (3) is prepared by thermal evaporation.

[0022] Preferably, the thickness of the silver electrode in step (3) is 100~110 nm, and it is prepared by thermal evaporation.

[0023] In this invention, both the cathode buffer layer and the silver electrode are prepared by thermal evaporation. This method has simple equipment and a high deposition rate, which helps to significantly reduce manufacturing costs and promote the large-scale mass production of perovskite solar cells.

[0024] A perovskite solar cell is prepared by the above-described method for preparing a perovskite solar cell based on a fullerene-based hybrid electron transport layer.

[0025] Compared with the prior art, the beneficial effects of the present invention include: This invention utilizes double-sphere fullerene L8BO-DC 60 A PCBM:L8BO-DC60 hybrid electron transport layer was constructed by incorporating PCBM and applied to an inverted perovskite solar cell. Experimental results show that this hybrid electron transport layer can effectively improve the film morphology, optimize interface energy level matching, enhance electron transport capability, and improve the photovoltaic performance and environmental stability of the device. Specifically, when L8BO-DC... 60 When the addition amount is 1~3 wt%, the performance of the hybrid transport layer is higher than that of the PCBM transport layer, exhibiting excellent optoelectronic performance. Attached Figure Description

[0026] Figure 1Atomic force microscopy (AFM) morphology and KPFM potential distribution diagram of the electron transport layer of the perovskite solar cell prepared in Comparative Example 1 and Example 2 are shown. The top row, from left to right, corresponds to the electron transport layer morphology of Comparative Example 1 and Example 2, respectively. The bottom row, from left to right, corresponds to the surface potential distribution diagram of the electron transport layer of Comparative Example 1, the surface potential distribution diagram of Example 2, and the statistical distribution diagram of the surface potential difference between Comparative Example 1 and Example 2, respectively.

[0027] Figure 2 Comparative Example 1 (PCBM) and Example 2 (PCBM: L8BO-DC) were prepared under dark, room temperature conditions. 60 A comparison of the conductivity and electron mobility of the perovskite electron transport layer prepared by [the study].

[0028] Figure 3 This is a comparison of the steady-state fluorescence (PL) and time-resolved fluorescence (TRPL) spectra of the "substrate / perovskite absorber / electron transport layer" structures in Comparative Example 1 and Example 2 at room temperature. The left image corresponds to the steady-state fluorescence spectrum, and the right image corresponds to the time-resolved fluorescence spectrum. In each image, PVSK corresponds to the substrate / perovskite absorber layer, PVSK / PCBM corresponds to the substrate / perovskite absorber layer / comparative Example 1 electron transport layer, and PVSK / L8BO-DC... 60 Corresponding substrate / perovskite light-absorbing layer / L8BO-DC 60 PVSK / PCBM: L8BO-DC 60 Corresponding substrate / perovskite light-absorbing layer / electron transport layer of Example 2.

[0029] Figure 4 Comparative Example 1 (PCBM) and Example 2 (PCBM: L8BO-DC) 60 The photoelectric conversion efficiency (PCE) and open-circuit voltage (OCV) of the perovskite solar cells prepared by ) V OC ), short-circuit current density ( J SC A comparison chart of the fill factor (FF) and the fill factor (FF); the left chart shows the results under both forward and reverse scans. J - V Characteristic curves, the right figure shows the EQE spectrum and integral short-circuit current density curve.

[0030] Figure 5 The image shows a comparison of the water contact angle test results for the "substrate / electron transport layer" structure in Comparative Example 1 and Example 2. The left image corresponds to Comparative Example 1, and the right image corresponds to Example 2.

[0031] Figure 6 Comparative Example 1 (PCBM) and Example 2 (PCBM: L8BO-DC) 60The photoelectric conversion efficiency (PCE) and open-circuit voltage (OCV) of the perovskite solar cells prepared by ) V OC ), short-circuit current density ( J SC A comparison chart of the changes in PCE and fill factor (FF) over 30 days. The top row, from left to right, corresponds to PCE and FF respectively, while the bottom row, from left to right, corresponds to... J SC and V OC . Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0033] The L8BO-DC described in this embodiment of the invention 60 The powder was prepared according to the method published in the following journal: C60-Terminated Acceptor Boosts Efficiency and Stability in Organic Solar Cells via Interfacial Manipulation. Advanced Materials, 2026. Example 1 A method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer, comprising the following specific steps: (1) The glass substrate plated with indium tin oxide (ITO) is cleaned, dried, and subjected to ultraviolet light treatment to obtain the pretreated substrate. (2) MeO-2PACz was dissolved in anhydrous ethanol to prepare a precursor solution. The precursor solution was spin-coated onto the pretreated substrate. The substrate was then annealed at 100 °C for 10 min and naturally cooled to room temperature to form a hole transport layer with a thickness of 5 nm. (3) Weigh 387.2 mg PbI2, 176.3 mg FAI, 53.0 mg CsI and 132.1 mg PbBr2, add them to 1 mL of a mixed solvent with a DMF:DMSO volume ratio of 4:1, and dissolve them completely to obtain a perovskite precursor solution. Stir the solution at room temperature for 6 h and filter it through a 0.22 μm filter membrane before use. Take 50 μL of the above perovskite precursor solution and dynamically drop it onto the surface of the hole transport layer. Spin coat it at 3000 rpm for 30 s. 5 s before the end of the spin coating, drop 100 μL of chlorobenzene as an antisolvent onto the surface of the perovskite wet film. Then, anneal the obtained perovskite film at 100 °C for 10 min in a glove box to obtain a perovskite light-absorbing layer with a thickness of 300 nm. (4) L8BO-DC 60 The powder was mixed with a 20 mg / mL PCBM chlorobenzene solution to obtain L8BO-DC. 60 A mixed solution with a concentration of 1 wt% was spin-coated onto the perovskite light-absorbing layer described in step (1), and dried to obtain a fullerene-based hybrid electron transport layer with a thickness of 50 nm. (5) Under vacuum conditions, 5 nm BCP and 100 nm silver electrodes are deposited on the surface of the fullerene-based hybrid electron transport layer by thermal evaporation to obtain a perovskite solar cell.

[0034] Example 2 A method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer, comprising the following specific steps: (1) The glass substrate plated with indium tin oxide (ITO) is cleaned, dried, and subjected to ultraviolet light treatment to obtain the pretreated substrate. (2) MeO-2PACz was dissolved in anhydrous ethanol to prepare a precursor solution. The precursor solution was spin-coated onto the pretreated substrate. The substrate was then annealed at 100°C for 10 min and naturally cooled to room temperature to form a hole transport layer with a thickness of 5 nm. (3) Weigh 387.2 mg PbI2, 176.3 mg FAI, 53.0 mg CsI and 132.1 mg PbBr2, add them to 1 mL of a mixed solvent with a DMF:DMSO volume ratio of 4:1, and dissolve them completely to obtain a perovskite precursor solution. Stir the solution at room temperature for 6 h and filter it through a 0.22 μm filter membrane before use. Take 50 μL of the above perovskite precursor solution and dynamically drop it onto the surface of the hole transport layer. Spin coat it at 3000 rpm for 30 s. 5 s before the end of the spin coating, drop 100 μL of chlorobenzene as an antisolvent onto the surface of the perovskite wet film. Then, anneal the obtained perovskite film at 100 °C for 10 min in a glove box to obtain a perovskite light-absorbing layer with a thickness of 300 nm. (4) L8BO-DC 60 The powder was mixed with a 20 mg / mL PCBM chlorobenzene solution to obtain L8BO-DC. 60 A mixed solution with a concentration of 2 wt% was spin-coated onto the perovskite light-absorbing layer described in step (1), and dried to obtain a fullerene-based hybrid electron transport layer with a thickness of 50 nm. (5) Under vacuum conditions, 5 nm BCP and 100 nm silver electrodes are deposited on the surface of the fullerene-based hybrid electron transport layer by thermal evaporation to obtain a perovskite solar cell.

[0035] Example 3 A method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer, comprising the following specific steps: (1) The glass substrate plated with indium tin oxide (ITO) is cleaned, dried, and subjected to ultraviolet light treatment to obtain the pretreated substrate. (2) MeO-2PACz was dissolved in anhydrous ethanol to prepare a precursor solution. The precursor solution was spin-coated onto the pretreated substrate. The substrate was then annealed at 100°C for 10 min and naturally cooled to room temperature to form a hole transport layer with a thickness of 5 nm. (3) Weigh 387.2 mg PbI2, 176.3 mg FAI, 53.0 mg CsI and 132.1 mg PbBr2, add them to 1 mL of a mixed solvent with a DMF:DMSO volume ratio of 4:1, and dissolve them completely to obtain a perovskite precursor solution. Stir the solution at room temperature for 6 h and filter it through a 0.22 μm filter membrane before use. Take 50 μL of the above perovskite precursor solution and dynamically drop it onto the surface of the hole transport layer. Spin coat it at 3000 rpm for 30 s. 5 s before the end of the spin coating, drop 100 μL of chlorobenzene as an antisolvent onto the surface of the perovskite wet film. Then, anneal the obtained perovskite film at 100 °C for 10 min in a glove box to obtain a perovskite light-absorbing layer with a thickness of 300 nm. (4) L8BO-DC 60 The powder was mixed with a 20 mg / mL PCBM chlorobenzene solution to obtain L8BO-DC. 60 A 3 wt% mixed solution was spin-coated onto the perovskite light-absorbing layer described in step (1), and dried to obtain a fullerene-based hybrid electron transport layer with a thickness of 50 nm. (5) Under vacuum conditions, 5 nm BCP and 100 nm silver electrodes are deposited on the surface of the fullerene-based hybrid electron transport layer by thermal evaporation to obtain a perovskite solar cell.

[0036] Comparative Example 1 A method for preparing a perovskite solar cell, comprising the following specific steps: (1) The glass substrate plated with indium tin oxide (ITO) is cleaned, dried, and subjected to ultraviolet light treatment to obtain the pretreated substrate. (2) MeO-2PACz was dissolved in anhydrous ethanol to prepare a precursor solution. The precursor solution was spin-coated onto the pretreated substrate. The substrate was then annealed at 100°C for 10 min and naturally cooled to room temperature to form a hole transport layer with a thickness of 5 nm. (3) Weigh 387.2 mg PbI2, 176.3 mg FAI, 53.0 mg CsI and 132.1 mg PbBr2, add them to 1 mL of a mixed solvent with a DMF:DMSO volume ratio of 4:1, and dissolve them completely to obtain a perovskite precursor solution. Stir the solution at room temperature for 6 h and filter it through a 0.22 μm filter membrane before use. Take 50 μL of the above perovskite precursor solution and dynamically drop it onto the surface of the hole transport layer. Spin coat it at 3000 rpm for 30 s. 5 s before the end of the spin coating, drop 100 μL of chlorobenzene as an antisolvent onto the surface of the perovskite wet film. Then, anneal the obtained perovskite film at 100 °C for 10 min in a glove box to obtain a perovskite light-absorbing layer with a thickness of 300 nm. (4) Spin-coat a chlorobenzene solution of PCBM with a concentration of 20 mg / mL onto the perovskite light-absorbing layer described in step (1), and after drying, obtain an electron transport layer with a thickness of 50 nm. (5) Under vacuum conditions, 5 nm BCP and 100 nm silver electrodes are deposited on the surface of the electron transport layer by thermal evaporation to obtain a perovskite solar cell.

[0037] The JV characteristic parameters of the perovskite solar cells prepared in Examples 1-3 and Comparative Example 1 were tested and summarized in Table 1.

[0038] Table 1 JV Characteristic Parameters

[0039] Referring to Table 1, we can see that the photoelectric conversion efficiency of the devices in Examples 1 to 3 is improved compared to Comparative Example 1. Among them, Example 2 exhibits the best overall performance, with a reverse scan PCE of 23.65% and a forward scan PCE of 23.48%, both significantly higher than Comparative Example 1's 21.73% and 20.77%, respectively. J - V In terms of characteristic parameters, the open-circuit voltage, short-circuit current density, and fill factor of the device in Example 1 are all better than those in Comparative Example 1, indicating that the modification treatment in this application can reduce internal defect recombination, promote carrier extraction and transport, and improve interface contact quality. Example 2 has the best performance, possibly because the amount of its modified material is within the optimal range, which can fully exert the effects of defect passivation and interface regulation while avoiding carrier transport obstruction caused by excessive modified material.

[0040] Figure 1Atomic force microscopy (AFM) morphology images and KPFM potential distribution diagrams of the electron transport layers of the perovskite solar cells prepared in Comparative Example 1 and Example 2 are shown. In the figures, the top row, from left to right, corresponds to the electron transport layer morphology images of Comparative Example 1 and Example 2, respectively. The bottom row, from left to right, corresponds to the surface potential distribution diagrams of the electron transport layers of Comparative Example 1, Example 2, and the statistical distribution diagram of the surface potential difference between Comparative Example 1 and Example 2, respectively. Figure 1 We can see that the surface roughness of the interface in Example 2 decreased from 5.9 nm to 5.6 nm, indicating that the introduction of 2 wt% L8BO-DC 60 Subsequently, the film quality of the electron transport layer was improved, and the interface coverage became more uniform and dense. Meanwhile, the film of Example 2 exhibited a higher and more uniform work function distribution, indicating that it is beneficial for optimizing the energy level matching between the electron transport layer and the perovskite light-absorbing layer, and reducing the interface charge transport barrier.

[0041] Figure 2 Comparative Example 1 (PCBM) and Example 2 (PCBM: L8BO-DC) were prepared under dark, room temperature conditions. 60 A comparison of the conductivity and electron mobility of the perovskite electron transport layer prepared in this study is shown. From left to right, the electron transport conductivity and electron mobility plots correspond to those of Example 1 and Example 2, respectively. The values ​​of conductivity and electron mobility were obtained by fitting the slopes of the curves in the figures. Figure 2 We can see that the conductivity of the hybrid thin film described in Example 2 is 5.7 × 10⁻⁶ compared to that of pure PCBM. -3 mS·cm -1 Increased to 6.9×10 -3 mS·cm -1 Electron mobility increased from 2.5 × 10⁻⁶ -4 cm 2 ·V -1 ·s -1 Upgraded to 3.0×10 -4 cm 2 ·V -1 ·s -1 This indicates that L8BO-DC 60 The introduction of [something] can significantly enhance electron transport capabilities.

[0042] Figure 3 The images show a comparison of steady-state fluorescence (PL) and time-resolved fluorescence (TRPL) spectra of the "substrate / perovskite absorber / electron transport layer" structures in Comparative Example 1 and Example 2 at room temperature. The left image corresponds to the steady-state fluorescence spectrum, and the right image corresponds to the time-resolved fluorescence spectrum. In each image, PVSK corresponds to the substrate / perovskite absorber layer, PVSK / PCBM corresponds to the substrate / perovskite absorber layer / electronic transport layer of Comparative Example 1, and PVSK / L8BO-DC...60 Corresponding substrate / perovskite light-absorbing layer / L8BO-DC 60 PVSK / PCBM: L8BO-DC 60 Corresponding substrate / perovskite light-absorbing layer / electron transport layer of Example 2. From Figure 3 We can see that, compared to standalone perovskite films, the introduction of PCBM and L8BO-DC... 60 Or PCBM: L8BO-DC 60 After the electron transport layer, the PL intensity decreased significantly, and the TRPL decay accelerated significantly, indicating that the electron transport layer can promote the transfer of photogenerated electrons from the perovskite absorber layer to the electron transport layer. Among them, Example 2 showed stronger PL quenching and faster fluorescence decay, indicating that it has better electron extraction capability and lower interfacial carrier recombination.

[0043] Figure 4 Comparative Example 1 (PCBM) and Example 2 (PCBM: L8BO-DC) 60 The photoelectric conversion efficiency (PCE) and open-circuit voltage (OCV) of the perovskite solar cells prepared by ) V OC ), short-circuit current density ( J SC A comparison chart of the fill factor (FF) and the fill factor (FF), where the left chart shows the results under both forward and reverse scans. J - V Characteristic curves, the right figure shows the EQE spectrum and integral short-circuit current density curve. From Figure 4 We can see that the above-mentioned indicators of Example 2 are all better than those of Comparative Example 1, which uses a pure PCBM electron transport layer. The external quantum efficiency (EQE) response is also further improved. At the same time, the hysteresis effect of Example 2 is significantly weakened, indicating that the hybrid electron transport layer is beneficial to improving the charge extraction and transport characteristics of the device.

[0044] Figure 5 The images show a comparison of water contact angle tests between the "substrate / electron transport layer" structures in Comparative Example 1 and Example 2, with the left image corresponding to Comparative Example 1 and the right image corresponding to Example 2. Figure 5 We can see that: the introduction of 2 wt% L8BO-DC 60 Subsequently, the water contact angle on the film surface increased from 83.4° to 91.1°, indicating that the hydrophobicity of the hybrid electron transport layer was enhanced, which helped to suppress the adverse effects of moisture on the perovskite light-absorbing layer.

[0045] Figure 6 Comparative Example 1 (PCBM) and Example 2 (PCBM: L8BO-DC) 60 The photoelectric conversion efficiency (PCE) and open-circuit voltage (OCV) of the perovskite solar cells prepared by ) V OC), short-circuit current density ( J SC A comparison chart of the changes in PCE and fill factor (FF) over 30 days. The top row, from left to right, corresponds to PCE and FF respectively, while the bottom row, from left to right, corresponds to... J SC and V OC The test conditions were: 25℃, 25-30% relative humidity, and a dark atmospheric environment. Figure 6 We can see that the device prepared in Example 2 still maintains 86% of the initial PCE, while the control device using a pure PCBM electron transport layer only maintains 76%, indicating that the hybrid electron transport layer can significantly improve the environmental stability of perovskite solar cells.

[0046] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer, characterized in that, Includes the following steps: (1) A hole transport layer and a perovskite light-absorbing layer are sequentially prepared on the pretreated substrate; (2) L8BO-DC 60 The powder was mixed with an organic solution of PCBM to obtain L8BO-DC. 60 A mixed solution with a concentration of 1~3 wt% was prepared; the mixed solution was spin-coated onto the perovskite light-absorbing layer described in step (1), and dried to obtain a fullerene-based hybrid electron transport layer. (3) A cathode buffer layer and a silver electrode are sequentially prepared on the fullerene-based hybrid electron transport layer described in step (2) to obtain a perovskite battery based on the fullerene-based hybrid electron transport layer.

2. The method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer according to claim 1, characterized in that, The substrate in step (1) is indium tin oxide conductive glass; and / or The substrate in step (1) undergoes the following pretreatment: sequential cleaning, drying, and ultraviolet light treatment.

3. The method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer according to claim 1, characterized in that, The thickness of the hole transport layer in step (1) is 5~10 nm; and / or The thickness of the perovskite light-absorbing layer in step (1) is 300 nm.

4. The method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer according to claim 3, characterized in that, The hole transport layer in step (1) is prepared by the following steps: MeO-2PACz is dissolved in anhydrous ethanol to prepare a precursor solution, the precursor solution is spin-coated onto the pretreated substrate, the substrate is then annealed and naturally cooled to room temperature to form a hole transport layer.

5. The method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer according to claim 1, characterized in that, The concentration of the organic solution of PCBM in step (2) is 20 mg / mL.

6. The method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer according to claim 5, characterized in that, The solute in the organic solution of the PCBM in step (2) is one of chlorobenzene, chloronaphthalene and o-dichlorobenzene.

7. The method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer according to claim 1, characterized in that, The thickness of the fullerene-based hybrid electron transport layer in step (2) is 50~60 nm.

8. The method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer according to claim 1, characterized in that, The thickness of the cathode buffer layer in step (3) is 5~7 nm; and / or The cathode buffer layer in step (3) is prepared by thermal evaporation.

9. The method for fabricating a perovskite solar cell based on a fullerene-based hybrid electron transport layer according to claim 1, characterized in that, The silver electrode in step (3) has a thickness of 100~110 nm and is prepared by thermal evaporation.

10. A perovskite solar cell, characterized in that, The perovskite solar cell based on a fullerene-based hybrid electron transport layer, as described in any one of claims 1 to 9, is prepared.